Paradigmas da Esquerda Brasileira:as quedas do Senador Prestes e dos Presidentes Goulart e Rousseff à luz de formulações de Maquiavel e Gramsci - Vernille, Victor Moraes (2020)
This dissertation studies the similarities of the Brazilian left in three moments: the rise and fall of PCB and Luiz Carlos Prestes to the end of Estado Novo, the deposition of João Goulart in 1964 and the impeachment of Dilma Rousseff in 2016. The objective is to understand as in these periods of ascension of this political spectrum the victories achieved could not be sustained in the long term and caused loss of power and early termination of the mandates